Identified protective factors to support psychological well-being among gender diverse autistic youth. Issue 2 (3rd April 2023) - Greenspan, Scott B.; Carr, Samuel; Woodman, Ashley C.; Cannava, Amy; Li, Yena
Abstract: Literature has discussed the intersectionality between autism and transgender and gender diverse (TGD) identities. Research has also identified the importance of protective factors, which are experiences that enhance positive outcomes in the face of potentially negative experiences. This exploratory quantitative survey study seeks to identify school and community-based protective factors that relate to psychological well-being and life satisfaction among 31 TGD Autistic youths between the ages of 13 to 17. The authors utilized adapted and full-forms of validated measures including the KID-SCREEN 27, Brief Multidimensional Students' Life Satisfaction Survey Peabody Treatment Progress Battery, Adolescent Resilience Questionnaire, Perceived Coronavirus Threat Questionnaire, and Autism-Spectrum Quotient. Results suggest that community connectedness, school support, family availability, and self-identification of sexual orientation as queer were identified as protective factors. Implications for research and practice are discussed.